COMMUNICATION STRATEGY IN SOCIALIZING OF SULTAN SYARIF HASYIM AS A TOURISM OBJECT (Study at the UPT KPHP Tahura Minas of Riau Forestry Office) - Febby Dwan Putra; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The attractions of the Taman Hutan akyat (TAHURA) will have no meaning without socialization, because socialization is the most important thing that must be done in order to convey messages or information to the public. According o the data from 2014-2017 the visitors to the Tahura Sultan Syarif Hasyim, experienced an increase in visits, but in 2018 there was a very drastic decline, which is very important to consider by conducting socialization. The purpose of this study was to determine the strategy of determining the communicator, the strategy of determining the audience, the strategy of determining the message and the choice of communication media strategy carried out by the KPHP UPT Tahura Minas of Riau Forestry Office in socializing the Taman Hutan Rakyat Sultan Syarif Hasyim as a tourism objects. This research use desciptive qualitative approach. The informants of this study were 8 people who were selected using the key person method. Types and sources of data consist of primary data and secondary data. The technique of collecting data is done by observing, interviewing and documenting. Data analysis techniques used Huberman and Miles Model data analysis, and data validity checking techniques were carried out by extending participation, triangulation and membership checking. The results of this study indicate that the strategy to determine communicators is by placing communicators who have credibility and knowledge of Tahura the Sultan Syarif Hasyim Forest Park as an attraction object as a whole. The strategy to determine the audience is the general public i.e. student, college student and local society. The strategy for determining messages is to emphasize the core message, and organize the message and message content is persuasive an informative. The media selection strategy is to use print media: i.e. newspapers, brochures and banners, and online media.